2017
DOI: 10.1371/journal.pone.0170420
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Drug Resistance Profiles of Patients Infected with CRF07_BC Using Phenotypic Assay and Ultra-Deep Pyrosequencing

Abstract: The usefulness of ultra-deep pyrosequencing (UDPS) for the diagnosis of HIV-1 drug resistance (DR) remains to be determined. Previously, we reported an explosive outbreak of HIV-1 circulating recombinant form (CRF) 07_BC among injection drug users (IDUs) in Taiwan in 2004. The goal of this study was to characterize the DR of CRF07_BC strains using different assays including UDPS. Seven CRF07_BC isolates including 4 from early epidemic (collected in 2004–2005) and 3 from late epidemic (collected in 2008) were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Unfortunately, there were a lack of studies available to address this question. More recently, Hung et al [39] reported that clinical CRF07_BC-7d isolates with the mutations in the protease (PR) region had obtained the resistance to protease inhibitors (PIs), including ritonavir, saquinavir, indinavir, nelfinavir, and amprenavir (resistant fold range 4.4-47.3). Some studies from mainland China indicate that potential drug-resistant mutants of Chinese CRF07_BC viruses (most isolates were non-amino acid deletion strains) were resistant to Nevirapine (NVP), which is the most frequently used antiretroviral drug in China [40].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there were a lack of studies available to address this question. More recently, Hung et al [39] reported that clinical CRF07_BC-7d isolates with the mutations in the protease (PR) region had obtained the resistance to protease inhibitors (PIs), including ritonavir, saquinavir, indinavir, nelfinavir, and amprenavir (resistant fold range 4.4-47.3). Some studies from mainland China indicate that potential drug-resistant mutants of Chinese CRF07_BC viruses (most isolates were non-amino acid deletion strains) were resistant to Nevirapine (NVP), which is the most frequently used antiretroviral drug in China [40].…”
Section: Discussionmentioning
confidence: 99%